2011
DOI: 10.7150/ijbs.7.376
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Mannich Base as a Novel Inhibitor of Mycobacterium Tuberculosis Isocitrate by High-Throughput Screening

Abstract: Mycobacterium tuberculosis (MTB) remains one of the most significant human pathogens since its discovery in 1882. An estimated 1.5 million people died from tubercle bacillus (TB) in 2006, and globally, there were an estimated 9.27 million incident cases of TB in 2007. Glyoxylate bypass pathway occurs in a wide range of pathogens and plays a key role in the pathogenesis of Mycobacterium tuberculosis. Isocitrate lyase (ICL) can catalyses the first step of this pathway, and reversibly cleaves isocitrate into succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Targeting vital metabolic pathways of dormant mycobacteria not present in mammalian cells is an obvious strategy. Isocitrate lyase, a key enzyme in the glyoxylate bypass pathway, is an attractive option although thus far efforts to target this enzyme have proven difficult[51]. One of the primary difficulties encountered by the bacillus in adapting to hypoxia is in disposing of excess reducing equivalents generated by both anabolic and catabolic processes [52].…”
Section: Targeting Dormant Mycobacteriamentioning
confidence: 99%
“…Targeting vital metabolic pathways of dormant mycobacteria not present in mammalian cells is an obvious strategy. Isocitrate lyase, a key enzyme in the glyoxylate bypass pathway, is an attractive option although thus far efforts to target this enzyme have proven difficult[51]. One of the primary difficulties encountered by the bacillus in adapting to hypoxia is in disposing of excess reducing equivalents generated by both anabolic and catabolic processes [52].…”
Section: Targeting Dormant Mycobacteriamentioning
confidence: 99%
“…Other than derivative synthesis, other categories of synthetic compound such as DNAzymes [ 41 ], Mannich bases [ 42 ], peptide inhibitors [ 43 , 44 ], and pyruvate-isoniazid analog with their copper complex [ 45 ] also gained some attention in the crowd. In 2005, the concept of silencing the icl gene by DNAzymes was introduced.…”
Section: Discovery Of Isocitrate Lyase Potential Inhibitors From Dmentioning
confidence: 99%
“…3d) were found to be the most potent inhibitors, with the inhibition constants (K i ) of 120, 190, 120, and 3 μM, respectively. In another study, IC 50 (the half maximal inhibitory concentration) of oxalate was determined as 0.013 M [41]. Oxalate and malate were also shown to suppress isocitrate lyase activity to approximately 50% at the concentration of 5 mM [53].…”
Section: Structural Analogues Of Metabolic Intermediates Ionsmentioning
confidence: 99%
“…Isocitrate lyase has been reported as one of the essential enzymes responsible for the growth of M. tuberculosis in activated macrophages and persistence in macrophages [40,41]. It has also been found that icl gene is vital for survival of M. tuberculosis in the lungs of infected mice during the persistent phase of infection (2-16 weeks), but it is not essential during the early and acute phase (0-2 weeks) of infection [40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation